Bailey, Gino i Espinosa, Felipe (2022). La ciudad de los lugares posibles - Sala, Eduard (Documents d'Anàlisi Geogràfica, 2023)
Bailey, Gino i Espinosa, Felipe (2022) La ciudad de los lugares posibles Barcelona: Hermenaute, 300 p. ISBN 9788412326949